PERAN BAHASA INDONESIA DAN BAHASA DAERAH DALAM PENDIDIKAN KARAKTER - Rina Devianty (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2017)
Languange has an important role in human life. Through languange humans can interact, communicate, and develop themselves. Languange also plays and important role and character education because languange can shape human characters. Languange is reflection of personality. The good or bad character of person is reflected in the person’s way when speaking. If someone is able to use the languange well, it will also affect his personality, nature, and character as well. A polite languange reflects the character of the Indonesian people. To reach the character of the nation, the next generation needs to be given the learning about the use of the good and the truth of  Indonesian languange, both orally and in writing.